Determinants of functional cure in interferon-treated chronic hepatitis B: a retrospective cohort analysis of HBsAg dynamics and clinical predictors - Zhou, Daqiong; Jia, Jianru; Zhao, Feng; Liu, Jiangyu; Zhang, Zichen; Cao, Zhenhuan (Frontiers in Cellular and Infection Microbiology, 2025)
Background and ObjectivesFunctional cure of chronic hepatitis B (CHB) is the optimal goal of antiviral therapy. This study evaluates the functional cure rates in a large cohort treated with interferon (IFNα) and explores baseline predictors to optimize personalized treatment strategies.MethodsThis retrospective study included CHB patients treated with IFN monotherapy or IFN combined with nucleos(t)ide analogs at Beijing You’an Hospital from 2008 to 2023. Patients were categorized into functional cure (FC) and non-functional cure (NFC) groups based on treatment outcomes.ResultsAmong 5288 patients, 887 (16.8%) achieved functional cure. FC patients had significantly lower baseline HBsAg, HBV DNA, and HBeAg positivity compared to NFC patients. Kaplan-Meier analysis revealed cumulative functional cure rates of 10.6%, 25.7%, and 39.9% at 48, 96, and 144 weeks, respectively. Multivariate logistic regression analysis identified lower baseline HBsAg levels, female, HBeAg negativity, lower γ-GT levels, and higher FT3 and FT4 levels as factors associated with higher functional cure rates. Patients with HBsAg <100 IU/ml had a cure rate of 58.8% within 96 weeks, compared to 11.1% for those with >1500 IU/ml.ConclusionEarly HBsAg decline is critical for functional cure. Female patients, HBeAg-negative status, and baseline HBsAg <100 IU/mL predict higher success rates.